EXPERIMENTALLY-CONTROLLED CARBON AND OXYGEN ISOTOPE EXCHANGE BETWEEN BIOAPATITES AND WATER UNDER INORGANIC AND MICROBIALLY-MEDIATED CONDITIONS - Zazzo A.; Lecuyer C.; Mariotti A. (My University, 2004)
Modern bone and enamel powders have reacted at 301 K with 13C- and 18O-labelled waters under inorganic and microbial conditions. The aim of the study is to investigate the resistance of stable isotope compositions of bioapatite carbonate (δ13C, δ18Oc) and phosphate (δ18Op) to isotopic alteration during early diagenesis. Rapid and significant carbon and oxygen isotope changes were observed in the carbonate and phosphate fractions of bone apatite before any detectable change occurred in the crystallinity or organic matter content. These observations indicate that chemical alterations of bone apatite are likely to start within days of death. Enamel crystallites are much more resistant than bone crystallites, but are not exempt of alteration. Non removable carbon and oxygen isotope enrichments were measured in the carbonate phase of bone (50-90%) and enamel (40%) after the acetic acid treatment. This result indicates that a significant part of 13C and 18O-labelled coming from the aqueous fluid has been durably incorporated into the apatite structure, probably through isotopic exchange or secondary carbonate apatite precipitation. As a result, acetic acid pre-treatments that are currently used to remove exogenous material by selective dissolution, are not adequate to restore pristine δ13C and δ18Oc values of fossil apatites. Under inorganic conditions, kinetics of oxygen isotope exchange are 10 times faster in carbonate than in phosphate. On the opposite, during biologically-mediated reactions, the kinetics of oxygen isotope exchange between phosphate and water is, at least, from 2 to 15 times faster than between carbonate and water. Enamel is a more suitable material than bone for paleoenvironmental or paleoclimatical reconstructions, but interpretations of δ18Op or δ13C values must be restricted to specimens for which no or very limited trace of microbial activity can be detected.